THE CONCEPT OF PEDAGOGICAL SKILLS, THEIR ROLE, AND IMPORTANCE IN THE TEACHER'S ACTIVITY - Nodira Saidova (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the stages of the formation of pedagogical skills of students, the views of historical oriental scholars on pedagogical ethics, and the professional qualities of a modern teacher.